Ionic liquids in biotransformations and organocatalysis solvents and beyond - Domínguez de María, Pablo, 1974- (Wiley, 2012)
"This book addresses the use of ionic liquids in biotransformation and organocatalysis. Its major parts include: an overview of the fundamentals of ionic liquids and their interactions with proteins and enzymes; the use of ILs in biotransformations; non-solvent applications such as additives, membranes, substrate anchoring, and the use of ILs in organocatalysis (from solvents to co-catalysts and new reactivities, as well as non-solvent applications such as anchoring and immobilization)"--Provided by publisher.